Identifying Risk Factors for Regional Recurrence in Early-Stage Breast Cancer with pT1-2 and Negative Sentinel Lymph Node Biopsy - You, Kai-yun (Cancer Manag Res, 2020)
BACKGROUND: Due to the low rate of regional recurrence (RR) in early-stage breast cancer with pT1-2 and negative sentinel lymph node biopsy (SLNB), no regional therapy is suggested for them. However, whether there is a subset of patients who were with high risk of regional failure and may benefit from regional treatment is still unknown. The current study was designed to identify the patients with high risk of RR, thereby providing clues for enhanced regional therapy. METHODS: We analyzed a total of 1124 breast cancer patients with pT1-2N0 from May 2004 to Dec 2014. All the patients were treated with breast-conservation surgery (BCS) and adjuvant whole-breast radiotherapy. The regional recurrence-free survival (RRFS), local regional recurrence-free survival (LRRFS), disease-free survival (DFS) and overall survival (OS) were assessed by using the Kaplan–Meier method. Cox proportional hazards regression was performed to detect factors in predicting the RRFS. RESULTS: In multivariable analysis, both T stage and molecular type were significant predictors of RRFS. Patients with T2 stage had a lower RRFS than those with T1stage. Triple-negative patients were more likely to suffer regional failure than the patients with other molecular types. The two predictors were then employed to divide all the patients into three groups based on the risk level of RR. Patients with both T2 and triple-negative molecular type had the lower RRFS, LRRFS, DFS and OS than the patients with one or no risk factor. CONCLUSION: For early-stage breast cancer patients with negative SLNB, those who were with both T2 stage and triple-negative molecular type had a high rate of RR and enhance regional therapy may be needed for them.